Analyzing the Effects of Epoxy Resin Based Sealer and Zinc Oxide Eugenol Sealers on the Fracture Resistance of Endodontically Treated Teeth: An in Vitro Comparative Study - Yeasmin, Rahela; Moral, Ali Asgor; Mujib, Sakib Ibn; Zahur, Tamanna; Sumaiya, Sarah Fatima (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The total closure of the root canal system and the removal of microbiological contaminants are the main objectives of root canal therapy. Solid core material and root canal sealers are essential components for achieving impermeable sealing of the root canal system and increasing the tooth's resistance to fracture. By conforming the stiff gutta-percha to the walls, these binding chemicals, also known as sealers, fill in the gaps, ancillary canals, and abnormalities in the canal, enabling the root to function as a single unit. This study compared the effects of Epoxy resin based sealer (AH Plus) and zinc oxide eugenol sealer on the ability of teeth that have undergone endodontic treatment to withstand fractures. Materials and methods: This was a quasi experimental study was conducted at BCSIR and Faculty of Dentistry of BSMMU, Dhaka from November 2020 to November 2021. Based on inclusion and exclusion criteria, forty recently extracted mandibular premolar teeth from humans were chosen. The pulp remnants were removed, the working length was measured, they were decoronated up to the cemento-enamel junction, and they underwent biomechanical preparation using the Protaper rotary file system up to F3. The teeth were then divided into two groups, each consisting of twenty teeth. divided into two groups, A and B, or subgroups, again. Subgroup A was obturated using the lateral condensation method, and subgroup B was obturated using the matched taper single cone method. Group 1 used Epoxy resin based sealer (AH Plus) (Dentsply, Germany) for obturation, while Group 2 used a zinc oxide-based eugenol-based sealer. Finally, they were positioned vertically in an acrylic resin block inside a custom-made mold holder, and their fracture strength was evaluated using a universal testing machine (Hounsfield, H1OKS, UK). Newtons were used to measure and analyze the force required to fracture. Significant results were reported as p-values, and an independent t-test was used for statistical analysis. Results: The result showed higher fracture resistance force values in group 1: Epoxy resin based sealer (AH Plus) than group 2: (Zinc oxide sealer) in both techniques. the fracture force was 462.02 ± 23.35 N and 363.6 ± 21.08 N in Group 1 subgroup A and subgroup B, respectively for lateral condensation technique.The fracture force for matched taper single-cone technique was 470.69 ± 34.69 N, 311.36 ± 118.42 N in Group 2 subgroup A and subgroup B, respectively. However, Compared to the zinc oxide sealer group, AH Plus sealer demonstrated a statistically significant difference (p<0.05). Conclusion: The lateral condensation approach and the matched taper single-cone technique suggest higher fracture load values for the AH Plus sealer group compared to the zinc oxide eugenol sealer group. JCMCTA 2023 ; 34 (2) : 128-133